Sleep quality in Spanish university professors: Association with lifestyle habits and physical and mental health indicators - Colado-Tello, María Estela; Dalmau-Torres, Josep María; Gargallo-Ibort, Esther; Jiménez-Boraita, Raúl (PlosOne, 2026)
Background :There is currently a growing interest in knowing the state of health of university professors. Sleep habits are essential for health and performance in any profession, including university teaching, and are related to different aspects of a teacher’s work productivity and general wellbeing. Objective: The study aimed to analyse sleep quality in Spanish university professors and to determine its association with lifestyle habits and physical and mental health indicators. Method The study was carried out on a sample of 1560 university professors (47.39 ± 11.29 years) from thirteen universities belonging to the Spanish Network of Health Promoting Universities. Sleep quality, emotional exhaustion, depersonalisation, self-fulfilment, quality of life, stress, anxiety, depression, vocal fatigue, sedentary time and eating behaviour were assessed. Results: Thirty-three percent of university professors were found to have poor sleep quality (95% CI: 30.7% - 35.3%). Significant differences were identified based on sociodemographic factors, particularly gender, with 74.9% of men reporting good sleep quality compared to 50.5% of women. According to the regression analysis, sleep problems were associated with less improvement in vocal symptoms after rest and lower quality of life scores. Additionally, they were linked to greater vocal fatigue, physical discomfort in the voice, female gender, and higher scores in mental health disorders (stress, anxiety, and depression). University professors with poor sleep quality also showed lower levels of physical activity, increased sedentary time, and higher levels of uncontrolled and emotional eating.Conclusions: Enhancing sleep quality and rest among university professors can boost cognitive and physical performance, foster better overall well-being, and lead to higher job satisfaction.
Keywords: health; university teachers; lifestyle habits; sleep